2021
DOI: 10.1002/jmv.26795
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID‐19 patients with bacterial coinfection admitted to the hospital from the emergency department in a large regional healthcare system

Abstract: Introduction: The rate of bacterial coinfection with SARS-CoV-2 is poorly defined.The decision to administer antibiotics early in the course of SARS-CoV-2 infection depends on the likelihood of bacterial coinfection.Methods: We performed a retrospective chart review of all patients admitted through the emergency department with confirmed SARS-CoV-2 infection over a 6-week period in a large healthcare system in the United States. Blood and respiratory culture results were abstracted and adjudicated by multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
0
18
0
8
Order By: Relevance
“…Specific bacteria commonly cited as causative agents of secondary infections included Staphylococcus spp. 9,10,[14][15][16][17][18]20,23,[27][28][29][30][31][32][33] , Streptococcus spp. 9,10,[15][16][17][18]20,23,27,29,34 , Escherichia coli 9,14,16,27,28,30,31,33,34 , Klebsiella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific bacteria commonly cited as causative agents of secondary infections included Staphylococcus spp. 9,10,[14][15][16][17][18]20,23,[27][28][29][30][31][32][33] , Streptococcus spp. 9,10,[15][16][17][18]20,23,27,29,34 , Escherichia coli 9,14,16,27,28,30,31,33,34 , Klebsiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported antibiotics in the literature reviewed were beta-lactams, macrolides and fluroquinolones 7,15,23,30 , in addition to piperacillin-tazobactam 9,23,24,26,29,30 and ceftriaxone 9,26,29,30,32 ; however, a wide range was reported (Table 2 and Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies [6,10,18,20,27,28,32,34,35,38,42,46,50,55] reported data on mortality in patients with COVID-19 and BSI. The pooled estimated occurrence of mortality (at the longest available follow-up) was 41% (95% CI 30%-52.8%; 189/482 patients; I 2 = 78%; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The authors screened 80 (14.7%) of 542 patients with COVID-19 for primary bacterial respiratory co-infection, of whom 15 (2.8%) were treated as having true primary respiratory co-infections, defined as any infection identified within 72 hour of admission. ( 9 ) Although we did not screen patients for viral co-infection, the rate has been reported to be 1.5–3.0%. ( 2 , 10 , 11 ) Respiratory syncytial virus and influenza A are the two most common, with detection rates of 16.9% and 15.5%, respectively.…”
Section: Discussionmentioning
confidence: 96%